Characterisation of Contemporary Slavery through the Analysis of Accommodation Conditions - Gairo Garreto; João Santos Baptista; Antônia Mota (Social Sciences, 2022)
Slave labour or work in conditions analogous to slavery continues on all continents and sometimes tends to be mistaken for “simple” violations of labour laws. Therefore, this work aims to identify parameters that allow distinguishing between situations of non-compliance with labour legislation and modern rural slavery in Brazil through the analysis of accommodation conditions. To achieve this objective, a bibliographic research was developed in six databases on sanitary, accommodation and clothing issues of enslaved workers in the 19th century in Brazil. The resulting data were compared with data from a sample of 392 proven cases of neoslavery detected between 2007 and 2017 in Brazil. The analysis focused on the general conditions of the physical structures necessary to protect workers against bad weather, animal attacks, violence, sanitary conditions to support physiological and asepsis needs, as well as the clothing provided and used. Similarities were found in the accommodation conditions between enslaved and neoenslaved workers in Brazil between the 19th and 21st centuries. The availability of sanitary conditions (toilets), rest (bedrooms/dormitories), and the general housing structure are very similar. Future research may point towards identifying other parameters and developing a tool to help authorities unequivocally identify neoslavery situations.